Assessing the efficiency of CFRP discrete confinement systems for concrete cylinders - Barros, Joaquim A. O. (2008)
Concrete columns requiring strengthening intervention always contain a certain percentage of steel hoops. Applying strips of wet lay-up carbon fiber reinforced polymer (CFRP) sheets in-between the existent steel hoops might, therefore, be an appropriate confinement technique with both technical and economic advantages, when full wrapping of a concrete column is taken as a basis of comparison. To assess the effectiveness of this discrete confinement strategy, circular cross section concrete elements confined by distinct arrangements of strips of CFRP sheet are submitted to a direct compression load up to the failure point. The influence of the width of the strip, distance between strips, number of CFRP layers per strip, CFRP stiffness and concrete strength class on the increase of the load carrying capacity and ductility of concrete columns, is evaluated. An analytical model is developed to predict the compressive stress-strain relationship of concrete columns confined by discrete and continuous CFRP arrangements. The main results of the experimental program are presented and analyzed and used to assess the model performance.